2020
DOI: 10.1080/07391102.2020.1764393
|View full text |Cite
|
Sign up to set email alerts
|

FDA-approved thiol-reacting drugs that potentially bind into the SARS-CoV-2 main protease, essential for viral replication

Abstract: Emergent novel SARS-CoV-2 is responsible for the current pandemic outbreak of severe acute respiratory syndrome with high mortality among the symptomatic population worldwide. Given the absence of a current vaccine or specific antiviral treatment, it is urgent to search for FDA-approved drugs that can potentially inhibit essential viral enzymes. The inhibition of 3CL pro has potential medical application, due to the fact that it is required for processing of the first translated replicase polyproteins into a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
93
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(99 citation statements)
references
References 43 publications
(57 reference statements)
2
93
0
2
Order By: Relevance
“…Disulfiram, an FDA-approved gasdermin D inhibitor, blocks SARS-CoV-2 replication in silico ( Lobo-Galo et al, 2020 ). Moreover, disulfiram was shown to abrogate gasdermin D pore formation by covalent bonding to Cys191/Cys192 ( Hu et al, 2020 ).…”
Section: Drugs Targeting Neutrophils For Covid-19 Associated Ardsmentioning
confidence: 99%
“…Disulfiram, an FDA-approved gasdermin D inhibitor, blocks SARS-CoV-2 replication in silico ( Lobo-Galo et al, 2020 ). Moreover, disulfiram was shown to abrogate gasdermin D pore formation by covalent bonding to Cys191/Cys192 ( Hu et al, 2020 ).…”
Section: Drugs Targeting Neutrophils For Covid-19 Associated Ardsmentioning
confidence: 99%
“…The first studies faced the problem that the crystallographic structure of SARS-CoV-2 3CLpro was not available and hence relied on homology modeling; 175 , 176 the experimental resolution of the 3CLpro structure boosted a huge increase in molecular docking studies. 176 180 , 192 …”
Section: Sars-cov-2 Proteasesmentioning
confidence: 99%
“… 122 González-Paz et al 192 performed a blind-docking study to predict the binding of the B1a and B1b forms of the wide-range antiparasitic drug ivermectin ( Figure 10 ) to 3CLpro, suggesting that ivermectin B1a binds with a higher affinity than ivermectin B1b. Lobo-Galo et al 180 used a multiscale approach in which blind docking was first used to pinpoint the principal potential binding cavities, most often corresponding to the active site, and this region was subsequently selected for further focused docking. The authors screened thiol-reacting FDA-approved drugs including captopril (antihypertensive drug) and found that disulfiram, used to treat chronic alcoholism, has promising antiviral properties ( Figure 10 ).…”
Section: Sars-cov-2 Proteasesmentioning
confidence: 99%
“…Another co-crystal (PDB-ID 6Y2F/6Y2G), a-ketoamide inhibitor (13b) is also reported recently, providing the structural and residue-based architecture of catalytic sites . These co-crystals are paving the route for the application of virtual screening (VS) to get more efficacious molecules (Al-Khafaji et al, 2020;Kumar et al, 2020;Lobo-Galo et al, 2020).…”
Section: Introductionmentioning
confidence: 99%